Qualitative insights into planning implementation of FeNO-guided asthma management in primary care - G. Lewis; K. Morton; M. Santillo; L. Yardley; K. Wang; B. Ainsworth; S. Tonkin-Crine (npj Primary Care Respiratory Medicine)
Abstract Fractional exhaled nitric oxide (FeNO) testing is used in primary care in some areas of the UK to aid asthma diagnosis but is used less frequently for managing asthma. A randomised controlled trial (RCT) is investigating whether an intervention, including FeNO testing and a clinical algorithm, improves outcomes for patients with asthma. This study was conducted to explore potential for implementation of the intervention. The study aim was to explore views of those with a vested interest in implementing the FeNO intervention into primary care asthma reviews. In-depth, semi-structured interviews were conducted online with individuals, including those with experience in policymaking, healthcare management, National Health Service commissioning, as healthcare professionals (HCPs) with extended roles, and patients and advocates. Inductive thematic analysis was conducted for nineteen interviews. Findings suggest complex interplay of barriers, contextual issues and facilitators. Overall, participants perceived FeNO-informed asthma management would enhance care, if used appropriately and flexibly according to context, for example planning implementation alongside remote reviews. Easier, equitable access to funded FeNO equipment would be needed for national implementation. Participants suggested motivation of all involved in future implementation may be increased by guidelines recommending FeNO, and by use of financial incentives and champions sharing best practice examples. In conclusion, financial obstacles were reiterated as a primary barrier to FeNO use. Despite barriers, facilitating implementation by harnessing prominent cost-benefits could persuade decision makers and clinicians. Findings lay early foundations for development of an implementation strategy.